(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2023)
It is well known how Leibniz turned his attention to a large number of domains in an attempt to demonstrate the universal interconnectedness of things. This essay aims to show the relationship between two areas of knowledge studied by Leibniz: gnoseology and biology. In particular, there is a close correspondence between the doctrine of innate ideas and that of the organism. The former are in fact understood as the constitutive elements of a layered mind and can be brought to consciousness through reminiscence. In contrast to the Platonic tradition, innate ideas are not the trace of notions acquired in previous lives, but are the result of a metamorphosis of living organisms. This consideration leads precisely to the Leibniz’s conception of the organism, influenced by the contemporary microscopic observation of van Leeuwenhoek and Malpighi and by the discovery of ‘spermatic animals’. In this sense, the idea of a pre-formed organism, subject to growth and contraction, is analogous to the peculiar conception of memory as a constitutive pre-configuration of the mind.